2012
DOI: 10.4049/jimmunol.1200079
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Cancer- and HIV Infection-Associated Endogenous Retrotransposable Elements Is Safe and Immunogenic

Abstract: The expression of endogenous retrotransposable elements including Long Interspersed Nuclear Element-1 (LINE-1 or L1) and Human Endogenous Retrovirus (HERV)-K accompanies neoplastic transformation and infection with viruses such as HIV. The ability to engender immunity safely against such self-antigens would facilitate the development of novel vaccines and immunotherapies. Here we address the safety and immunogenicity of vaccination with these elements. We employed immunohistochemical analysis and literature-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 62 publications
(67 reference statements)
2
58
0
Order By: Relevance
“…The etiology of these unusual features is unclear but may be related to clonal deletion of higher-avidity HERV-K(HML-2)-specific T cells. In this regard, it is interesting to note that when we have vaccinated mice against murine L1 retrotransposable element antigens, we have observed that robust T cell responses were detectable upon screening with overlapping 9-mer peptides, while, in parallel, a complete lack of responses was observed with overlapping 15-mer peptides (30). Comprehensive evaluation of HERV-K(HML-2)-specific T cell responses may therefore require the application of more sensitive methods, such as DC-mediated expansions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The etiology of these unusual features is unclear but may be related to clonal deletion of higher-avidity HERV-K(HML-2)-specific T cells. In this regard, it is interesting to note that when we have vaccinated mice against murine L1 retrotransposable element antigens, we have observed that robust T cell responses were detectable upon screening with overlapping 9-mer peptides, while, in parallel, a complete lack of responses was observed with overlapping 15-mer peptides (30). Comprehensive evaluation of HERV-K(HML-2)-specific T cell responses may therefore require the application of more sensitive methods, such as DC-mediated expansions.…”
Section: Discussionmentioning
confidence: 93%
“…In moving toward developing this vaccine strategy, it is important to consider whether immune tolerance to HERV-K(HML-2) antigens is likely to exist and, if so, whether breaking such tolerance may carry the risk of inducing autoimmunity. While HERV-K(HML-2) RNA appears to be readily detected in all tissues, including the thymus (33), we are of the position that the expression of HERV-K(HML-2)-Gag and -Env protein has not been convincingly demonstrated in any healthy adult human tissue, despite extensive screening (30). The fact that we are not able to more readily detect T cell responses to these antigens in HIV-1-infected individuals using 15-mers may be indicative of tolerance (29).…”
Section: Discussionmentioning
confidence: 95%
“…The safety and immunogenicity of such a vaccine were already demonstrated in nonhuman primates (15). Modulating HERV-K-specific humoral immunity may represent a novel approach in the quest to prevent and eradicate HIV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
“…This issue is crucial if Gag is to be used as a target for immunotherapies. Notably, vaccines against endogenous retroviruses are generally considered safe [17], although any specific vaccine will require individual testing for adverse effects, especially unintended autoimmunity. For their application, two scenarios may be envisioned.…”
Section: Expert Opinionmentioning
confidence: 99%